A potential role for olanzapine in the treatment of hyperemesis gravidarum. (12th December 2022) - Sharma, Verinder; Sharma, Sapna; Hutson, Janine; Martin, Alex
Abstract: Hyperemesis gravidarum is a rare but potentially serious complication of pregnancy. Some women with severe symptoms and possibly psychiatric comorbidities remain symptomatic despite the use of currently available treatments. Due to its favorable safety profile, antiemetic efficacy in other conditions, and 5-HT3 antagonism, olanzapine may be a potentially useful addition to the armamentarium for management of hyperemesis gravidarum resistant to standard- of-care treatment.